Nutritional management contributes to improvement in minimal hepatic encephalopathy and quality of life in patients with liver cirrhosis: A preliminary, prospective, open‐label study. Issue 5 (20th September 2012) - Kato, Akinobu; Tanaka, Hiroto; Kawaguchi, Takumi; Kanazawa, Hidenori; Iwasa, Motoh; Sakaida, Isao; Moriwaki, Hisataka; Murawaki, Yoshikazu; Suzuki, Kazuyuki; Okita, Kiwamu
<x xml:space="preserve">Abstract</x> Aim Problems in patients with minimal hepatic encephalopathy (MHE) include episodes such as falls and deficient driving skills, without any recognition of neurophysiological dysfunction. Patients with MHE are also more likely to develop overt hepatic encephalopathy. However, there is not yet any interventional strategy for MHE involving nutritional management. We conducted a preliminary study to investigate the proportion of positive MHE and the effects of nutritional management on MHE. Methods Patients with viral liver cirrhosis and abnormal neuropsychological tests were included. Nutritional consultations were conducted periodically by a dietitian, who recommended 30–35 kcal with 1.0–1.5 g of protein/kg of ideal bodyweight/day. The primary end‐point was to evaluate the proportion of patients who recovered from MHE. The secondary end‐point was to evaluate the improvement in the patients' quality of life (QOL). Results Thirty‐two (30.1%) of 106 patients were diagnosed with MHE. Nineteen patients were enrolled in the study. Eleven of 19 patients became non‐MHE after 4 weeks, and 13 of 19 patients (68.4%, P < 0.001) after 8 weeks. The mental summary scores were significantly improved at 8 weeks (P = 0.0413). Changes in albumin levels from week 0 to week 8 were 0.15 ± 0.16 g/dL in the improved MHE group and −0.28 ± 0.33 g/dL in the non‐improved MHE group, which differ significantly (P = 0.0130). Conclusion Periodical nutritional management improved MHE and QOL. Improving the patient's nutritional condition may be one approach to treating MHE.